THE EFFECT OF ENTREPRENEURIAL COMPETENCE AND PRODUCT INNOVATION ON COMPETITIVE ADVANTAGE AT DPC MEDAN WOMEN ENTREPRENEUR ASSOCIATION (IWAPI) - Muhammad Faisal; Indriani Adha; Khairunnisa; Clarissa Tarigan; Sari Wulandari (International Conference on Health Science, Green Economics, Educational Review and Technology, 2023)
This study aims to determine and analyze the effect of entrepreneurial competence and product innovation on competitive advantage at the DPC of the Indonesian Businesswomen Association of Medan. The method used in this research is quantitative descriptive method. The population in this study were members of the DPC of the Indonesian Businesswomen's Association of Medan, totaling 314 people. This study uses probability sampling techniques in simple random sampling in determining the sample. To determine the number of samples using the Slovin formula so that 76 respondents were obtained. Data processing in this study using the SPSS software program (version 27). The data analysis techniques used in this study are validity and reliability tests, Multiple Linear Regression Analysis, Classical Assumption Test, t test and F test, and Determination Coefficient Test. The results obtained from the data processing carried out are partially competent.